2017
DOI: 10.1111/bph.13747
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signalling through L‐type calcium channels: role in pathophysiology of spinal nociceptive transmission

Abstract: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 135 publications
0
56
0
Order By: Relevance
“…It is also possible to co‐culture DRG and spinal cord neurons to investigate nociceptive function (Yu et al ., ). Postsynaptic expression of Ca V 1 family voltage‐gated Ca 2+ channels in the dorsal horn may also contribute to maintenance of pathological pain (Roca‐Lapirot et al ., ). Thus, the Ca V 1.2 channel is expressed somatically and at proximal dendritic shafts, and Ca V 1.3 channels at distal somato‐dendritic compartments.…”
Section: Measuring Ion Channel Function In Nociceptive Pathwaysmentioning
confidence: 97%
“…It is also possible to co‐culture DRG and spinal cord neurons to investigate nociceptive function (Yu et al ., ). Postsynaptic expression of Ca V 1 family voltage‐gated Ca 2+ channels in the dorsal horn may also contribute to maintenance of pathological pain (Roca‐Lapirot et al ., ). Thus, the Ca V 1.2 channel is expressed somatically and at proximal dendritic shafts, and Ca V 1.3 channels at distal somato‐dendritic compartments.…”
Section: Measuring Ion Channel Function In Nociceptive Pathwaysmentioning
confidence: 97%
“…We assessed the role of ILs in windup of the flexion reflex, using two different families of blockers [14]. First, we applied 100 µg of verapamil, a blocker of the phenylalkylamine family.…”
Section: Windup Of the Flexion Reflex Is Sensitive To Il Blockers Inmentioning
confidence: 99%
“…Repetitive nociceptive stimulations of the ipsilateral paw elicit a windup of nociceptive flexion. It has been shown that windup of the flexion reflex in juvenile rats depends on a synaptic balance between excitation and inhibition that allows expression of intrinsic properties [11,13,14]. However, the flexion reflex is the output of a neural circuit that comprises both DHNs and motor neurons, and the latter ones also exhibit a windup of their discharge that presents the same molecular sensitivity as windup of DHNs [8,9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Intrathecal delivery preclinically of channel blockers (nifedipine, verapamil and benzothiazepines) have shown efficiency in altering injury induced hyperpathia. 73 …”
Section: Survey Of Current Targets Of Pain Therapeuticsmentioning
confidence: 99%